Accelerated Graphical User Interfaces - Navrátil, Ladislav (Vysoké učení technické v Brně. Fakulta informačních technologií, 2023)
Tato práce je zaměřena na multiplatformní grafická uživatelské rozhraní a jejich hardwarovou akceleraci. Popisuje, co to uživatelské rozhraní jsou a srovnává nástroje na jejich tvorbu  a způsoby jejich realizace. Hlavním bodem je vlastní návrh a implementace nástroje na tvorbu multiplatformních hardwarově akcelerovaných grafických uživatelských rozhraní. Srovnává vlastní koncept s existujícími řešeními, a uvádí ho do praxe na projektu s externí firmou.

This thesis is focused on a multi-platform graphical user interface and its hardware acceleration. It describes what the user interfaces are, it compares the tools used for their creation, and the methods of their realization. The main focus is a custom design and implementation of tools used for creating a cross-platform hardware accelerated graphical user interface. It compares my own concept with existing solutions, and places it into practice on a project with an external company.
Accelerated Graphical User Interfaces
Keywords: Grafická uživatelské rozhraní; Hardwarová akcelerace; OpenGL; OpenGL ES; GUI; Graphical user interface; Hardware acceleration; OpenGL; OpenGL ES; GUI